Applying Elsa Speak with Mobile-Assisted Language Learning (MALL) to Improve Students’ Speaking Achievement - Dini Juniarti; Dio Resta Permana; Jaya Nur Iman (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Speaking is one of the most essential skills in English learning; however, many students in English as a Foreign Language (EFL) contexts still experience difficulties in developing speaking proficiency due to limited opportunities for practice and teacher-centered instruction. At SMA Aziziah Palembang, students showed low performance in fluency, pronunciation, and confidence during speaking activities. This study investigated the effectiveness of the ELSA Speak application combined with the Mobile-Assisted Language Learning (MALL) strategy in improving students’ speaking skills. A quasi-experimental design employing a pre-test and post-test control group was applied to two tenth-grade classes. The experimental group received instruction through ELSA Speak-based activities, while the control group was taught using conventional methods. Students’ speaking performance was assessed in fluency, pronunciation, grammar, vocabulary, and comprehension using a rubric adapted from Brown (2004). The findings revealed that the experimental group’s mean score improved from 14.75 to 15.75, while the control group showed only a slight increase from 13.53 to 13.69. The improvement in the experimental group was particularly evident in pronunciation and fluency. Nevertheless, statistical analysis indicated no significant difference between the groups (p 0.05), which may have been influenced by the short treatment duration and limited access to smartphones for practice. Despite this limitation, the study highlights the potential of integrating ELSA Speak and the MALL strategy to support speaking development in EFL classrooms. The study contributes to the growing discussion on technology-assisted language learning and provides implications for future English speaking instruction.